2021
DOI: 10.1002/cam4.4481
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of pyrotinib in treating HER2‐positive breast cancer patients with brain metastasis: A multicenter study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
3
5
1
Order By: Relevance
“… 16–18 Thus, we consider ADCs and TKIs are both favorable options for this kind of patient. In this real-world study, pyrotinib-based therapy resulted in an mPFS of 11.6 months in patients with brain metastases, which is highly consistent with that of 11.3 months and 11.1 months reported in the PERMEATE study and by Gao et al for pyrotinib plus capecitabine in patients with brain metastases from HER2-positive MBC, 19 , 20 respectively. Although the prognosis of patients with brain metastases remains poor, treatment strategies range from local to systemic anti-HER2 therapies.…”
Section: Discussionsupporting
confidence: 89%
“… 16–18 Thus, we consider ADCs and TKIs are both favorable options for this kind of patient. In this real-world study, pyrotinib-based therapy resulted in an mPFS of 11.6 months in patients with brain metastases, which is highly consistent with that of 11.3 months and 11.1 months reported in the PERMEATE study and by Gao et al for pyrotinib plus capecitabine in patients with brain metastases from HER2-positive MBC, 19 , 20 respectively. Although the prognosis of patients with brain metastases remains poor, treatment strategies range from local to systemic anti-HER2 therapies.…”
Section: Discussionsupporting
confidence: 89%
“…In this meta-analysis, 9 studies investigating pyrotinib in a total of 321 Asian patients were included ( Table 4 ); 1 double blind phase 3 study [ 71 ], 1 single arm phase 2 trial [ 78 ] and 7 retrospective studies [ 70 , 72 , 73 , 74 , 75 , 76 , 77 ]. Pooled ORR was 43% (95% CI 27–59%; I 2 80%) ( Figure 2 E).…”
Section: Resultsmentioning
confidence: 99%
“…Another real-world study reported various efficacy indicators of pyrotinib-based therapy in 42 patients with ABC suffering from brain metastases. ORR was 40.4%, disease control was obtained in 92.8% of cases, improvement in intracranial symptoms was noted in all patients, the median duration of intracranial improvement was 15 months, the median time to relieve brain metastases was 43 days, the median time to relieve other metastases was 50 days, the median time to progression of brain metastases was 16.6 months, and the median time to disease progression was 11.1 months [ 67 ]. In a retrospective study involving 61 HER2-positive patients with brain metastases treated by pyrotinib-based regimens, median PFS was 8.6 months, median OS was 18.0 months, and the combination of pyrotinib with nab-paclitaxel was superior to the combination with capecitabine and vinorelbine with respect to PFS and OS.…”
Section: Clinical Evidence Of Pyrotinib In Abcmentioning
confidence: 99%